Traditional Fishermen in the Development of the Coastal Tourism Area in Sumatera Barat - Putra, Rinaldi Eka (Universitas Negeri Semarang, 2020)
Mandeh tourism area is a tourist area located on the coast, which was developed into a major tourist destination in the Pesisir Selatan District, West Sumatra Province. The Mandeh area people are mostly poor fishermen who depend on fishing by fishing. The development of the mandeh area as a tourist destination besides providing economic opportunities for the fishing community also requires the ability to adapt to respond to these changes. This study aims to analyze how traditional fishermen adapt to the development of the Mandeh tourism area to improve their standard of living. The research uses a qualitative approach, the data is taken by in-depth interviews, observations, and document studies. Interviews were conducted with traditional fishermen as informants. The study was conducted in the Mandeh area, on Carocok Beach, Pesisir Selatan Regency. The results showed that the adaptive capacity of traditional fishing communities was quite high, fishermen were quite responsive to environmental changes that occurred in the Mandeh area through a variety of strategies. The strategy carried out by traditional fishermen is to utilize social relationships in the community, take advantage of new economic opportunities, change the Fishing Area or